Attentional eye selection modulates sensory eye dominance. (November 2021) - Wang, Mengxin; McGraw, Paul; Ledgeway, Timothy
Abstract: Brief periods of monocular deprivation significantly modify binocular visual processing. For example, patching one eye for a few hours alters the inter-ocular balance, with the previously patched eye becoming dominant once the patch is removed. However, the contribution of higher-level visual processing to this phenomenon is still unclear. Here, we compared changes in sensory eye dominance produced by three types of monocular manipulations in adult participants with normal binocular vision. One eye was covered for 150 min using either an opaque patch, a diffusing lens, or a prism that inverted the image. All three manipulations altered dominance duration and predominance during binocular rivalry (BR) in favour of the treated eye and the time courses of the changes were similar. These results indicate that modifications of luminance or contrast are not strictly necessary to drive shifts in eye dominance, as both were unaltered in the prism condition. Next, we found that shifts in eye dominance were dependent on attentional demands during the monocular treatment period, providing support for the role of attentional eye selection in modulating eye dominance. Finally, we found relatively rapid build-up of the ocular dominance shift after the onset of monocular treatment. Taken together, our results suggest that modifications to monocular input alter inter-ocular balance via selective attentional mechanisms that bias output towards the deprived eye. Eye-based attention may play an important role in conditions where normal input to one eye is disrupted, such as childhood amblyopia.